Robert Wise the motion pictures - Jordan, J.R (BearManor Media, 2020)
Jordan examines the body of Wise's work in a film-by-film journey, his information woven neatly with interviews of participants providing the voices
Newly revised and updated
Keywords: Wise, Robert -- 1914-2005; Wise, Robert / 1914-2005; Motion picture producers and directors / History and criticism; Motion pictures / History; Biografie